Influence of jet-jet interaction on droplet size and jet instability in immiscible liquid-liquid system - Parmar, Harisinh Bhikhubhai; Pareek, Vishnu; Phan, Chi; Evans, G. (Pergamon, 2015)
This work investigates the effects of multiple jet interactions and single jet instability on jet breakup and droplet size using experimental and computational techniques. In particular, the jet separation distance, jet breakup length and droplet diameter were measured as a function of initial nozzle separation distance and jet volumetric flow rate. It was found that the two jets moved closer to each other to reach an equilibrium separation distance that was approximately 70% of the spacing between the two nozzles. The distance at which the instabilities were first observed on the surface of the jet was also a function of the initial separation distance. However, it was weakly dependent on the jet velocity. The jet breakup length and resultant droplet diameter were both influenced by flow rate and nozzle separation distance. The jet breakup length was found to decrease with reduction in nozzle spacing at the high flow rates. Interestingly, a linear relationship between droplet diameter and breakup length was found that was largely independent of nozzle spacing and consist with conventional Rayleigh jet breakup theory. The implications of the experimental observations on the design of multi-jet systems are discussed. Furthermore, computational fluid dynamics simulations were also used to identify the mechanism and dynamics of jet instability in the single jet systems. The simulation results were analysed to study the effect of instability on various parameters such as jet breakup, droplet formation and size of emulsion droplets. It was found that at higher volumetric flow rates, the droplets size increased during the jet breakup due to an asymmetric instability. The asymmetric instability was caused by the pressure gradient in the continuous phase and was prevented in double jet systems.